The MK2 cascade regulates mGluR-dependent synaptic plasticity and reversal learning. (1st September 2019) - Privitera, Lucia; Hogg, Ellen L.; Gaestel, Matthias; Wall, Mark J.; Corrêa, Sonia A.L.
Abstract: The ability to either erase or update the memories of a previously learned spatial task is an essential process that is required to modify behaviour in a changing environment. Current evidence suggests that the neural representation of such cognitive flexibility involves the balancing of synaptic potentiation (acquisition of memories) with synaptic depression (modulation and updating previously acquired memories). Here we demonstrate that the p38 MAPK/MAPK-activated protein kinase 2 (MK2) cascade is required to maintain the precise tuning of long-term potentiation and long-term depression at CA1 synapses of the hippocampus which is correlated with efficient reversal learning. Using the MK2 knockout (KO) mouse, we show that mGluR-LTD, but not NMDAR-LTD, is markedly impaired in mice aged between 4 and 5 weeks (juvenile) to 7 months (mature adult). Although the amplitude of LTP was the same as in wildtype mice, priming of LTP by the activation of group I metabotropic receptors was impaired in MK2 KO mice. Consistent with unaltered LTP amplitude and compromised mGluR-LTD, MK2 KO mice had intact spatial learning when performing the Barnes maze task, but showed specific deficits in selecting the most efficient combination of search strategies to perform the task reversal. Findings from this study suggest that the mGluR-p38-MK2 cascade is important for cognitive flexibility by regulating LTD amplitude and the priming of LTP. Highlights: The MK2 cascade regulates mGluR-mediated synaptic plasticity. The mGluR-p38-MK2 cascade as a novel mechanism to prime LTP. MK2 knockout mice are unable to reverse a previously learned hippocampal-dependent spatial task.